Multiple CD11c+ cells collaboratively express IL-1β to modulate stromal vascular endothelial growth factor and lymph node vascular-stromal growth() - Benahmed, Fairouz (2014)
Lymphadenopathy in autoimmune and other lymphoproliferative diseases is in part characterized by immunoblasts and vascular proliferation. The lymph node vasculature, along with the nonvascular stromal compartment, supports lymphocyte function, and targeting vascular-stromal expansion in inflamed nodes may modulate lymphocyte function in disease. CD11c(+) cells are essential for vascular-stromal proliferation and the upregulation of vascular endothelial growth factor (VEGF) needed for vascular proliferation. However, targetable CD11c(+) cell-derived molecular mediators, the identity of relevant CD11c(+) cells, and whether CD11c(+) cells directly stimulate VEGF-expressing stromal cells are poorly understood. In this study we show that CD11c(+) CD11b(+) CCR2-dependent monocytes and CCR7-dependent dendritic cells express IL-1β. IL-1β blockade, IL-1β deficiency in radiosensitive cells, and CCR2/CCR7 double deficiency but not single deficiency all attenuate immunization-induced vascular-stromal proliferation. gp38(+) stromal fibroblastic reticular cells (FRCs) that express VEGF are enriched for Thy1(+) cells and partially overlap with CCL21-expressing FRCs, and FRC VEGF is attenuated with IL-1β deficiency or blockade. IL-1β localizes to the outer borders of the T zone, where VEGF-expressing cells are also enriched. Ex vivo, CD11b(+) cells enriched for IL-1β(+) cells can directly induce cultured gp38(+)Thy1(+) FRCs to upregulate VEGF. Taken together, these results suggest a mechanism whereby multiple recruited CD11c(+) populations express IL-1β and directly modulate FRC function to help promote the initiation of vascular-stromal growth in stimulated lymph nodes. These data provide new insight into how CD11c(+) cells regulate the lymph node vascular-stromal compartment, add to the evolving understanding of functional stromal subsets, and suggest a possible utility for IL-1β blockade in preventing inflammatory lymph node growth.